Islamic Financing Risk Identification and Management in a Frontier Sharia Pawn Financing Context - Hidayah, Nurul; Adiaman, Andini; Hidayatina (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2025)
This study examines the identification and management of Islamic financing risks at PT Pegadaian Syariah Klademak Branch in Sorong, Southwest Papua, categorized as frontier (3T) region of Indonesia. A qualitative case study with thematic analysis approach was used to collect data through in-depth interviews with manager, officers and customers along with the document observation and analysis. According to the findings, financing risk can be divided into four main categories: financing, operational, reputational, and compliance. One of the most significant findings concerns financing risk, particularly in the Arum Haji financing product. This demonstrates that financing evaluation techniques that assess religious perspectives rather than a customer's ability to repay debt are considered irrelevant. The study also found that Pegadaian Syariah Klademak has implemented flexible risk management based on Islamic principles, as assessed by its flexible payment settlement process, humanistic communication, proactive reminders to customers to make timely payments, and active monitoring. Customers also trust the institution because they are honest and transparent, particularly in the collateral valuation process. Problems with repayment are generally caused by unstable customer behavior and income. These findings demonstrate the importance of financial literacy and behavioral interventions in Islamic financing risk mitigation and offer empirical insights from a frontier area context, it also provides recommendations for enhancing the effectiveness of risk management while maintaining institutional resilience, financial inclusion, and Sharia compliance.